Perfection and Success - Hasko von Kriegstein (Ergo, An Open Access Journal of Philosophy)
According to reductivist axiological perfectionism about well-being (RAP), well-being is constituted by the development and exercise of central human capacities. In defending this view, proponents have relied heavily on the claim that RAP provides a unifying explanation of the entries on the ‘objective list’ of well-being constituents. I argue that this argument fails to provide independent support for the theory. RAP does not render a plausible objective list unless such a list is used at every stage of theory development to shape the details of the view. Absent such motivated fine-tuning, RAP even fails to provide a satisfying account of two supposed paradigm cases of perfectionist value: achievement and knowledge. Thus, if RAP is to be defended, it must be defended directly by providing reasons for accepting the axiological principle at its heart. It cannot be defended, indirectly, by pointing to its attractive implications.